PENGARUH DOSIS PUPUK KANDANG SAPI DAN MACAM MULSA TERHADAP HASIL TANAMAN TOMAT (Solanum lycopersicum, L.) VARITAS KALIURANG - Muhammad Ichsannudin; Gembong Haryono; Yulia Eko Susilowati (Universitas Tidar, 2017)
The research about the effort of increasing the ried of plant tomato (Solanum lycopersicum, L.) which varieties Kaliurang with kind of mulch and cow manure dose was carried out on March 13rd until July 23rd, 2016. The location of this research was carried at Dlimas Village, Tegalrejo District, Magelang Regency. The altitude of location is 478 meters above sea level and the soil type is latosol with pH of 6,8. The experiment was conducted by using a factorial (3x3) that was arranged in a complete randomized block design, repeated three times. The first factor is manure dose 15, 20 and 25 ton/ha. The second factor is the mulching material from non mulch, black plastic and silver mulch. The result of the research shows that the optimum dose of cow manure 19,61 ton/ha increases height of plant, optumum dose 20,33 ton/ha increases fruit weight, optimum dose 22 ton/ha increases number of fruits per plant and optimum dose of 15 ton/ha increases weight per fruit. The use of mulch can increases the weight of fruit, number of fruits per plant and fresh weight of straw. The combination of silver plastic mulch and cow manure dose 15 ton/ha gives the highest yield at weight per fruit.